Genome-wide DNA methylation differences according to oestrogen receptor beta status in colorectal cancer - Neumeyer, Sonja; Popanda, Odilia; Edelmann, Dominic; Henschel, Katja; Toth, Csaba; Roth, Wilfried; Bläker, Hendrik; Jiang, Ruijingfang; Herpel, Esther; Jäkel, Cornelia; Schmezer, Peter; Jansen, Lina; et al. (Epigenetics, 2019)
Involvement of sex hormones in colorectal cancer (CRC) development has been linked to oestrogen receptor β (ERβ). Expression of ERβ is found reduced in tumour tissue and inversely related to mortality. However, mechanisms are not well understood. Our study aimed to detect differentially methylated genes associated with ERβ expression, which could point to mechanisms by which ERβ could influence risk and prognosis of CRC. Epigenome-wide DNA methylation profiling was performed using Illumina HumanMethylation450k BeadChip arrays in two independent tumour sample sets of CRC patients recruited in 2003-2010 by the German DACHS study (discovery cohort n = 917, replication cohort n = 907). ERβ expression was measured using immunohistochemistry and scored as negative, moderate and high. Differentially methylated CpG sites and genomic regions were determined using limma in the R-package RnBeads. For the comparison of tumours with moderate/high ERβ versus negative expression, differentially methylated CpG sites were identified but not confirmed by replication. Comparing tumours of high with tumours of negative ERβ expression revealed 2,904 differentially methylated CpG sites of which 403 were replicated (FDR adjusted p-value<0.05). Replicated CpGs were annotated to genes such as CD36, HK1 or LRP5. A survival analysis indicates that 30 of the replicated CpGs are also associated with overall survival (FDR-adjusted p-value<0.05). The regional analysis identified 60 differentially methylated promotor regions. The epigenome-wide analysis identified both novel genes as well as genes already implicated in CRC. Follow-up mechanistic studies to better understand the regulatory role of ERβ could inform potential targets for improving treatment or prevention of CRC.
Gesehen am 20.03.2020